Uma jornada de transformação pessoal e profissional de um Estudante-Estagiário - Filipe Manuel Fernandes Ferreira (2024)
The professional school placement is a crucial stage in the training of preservice teachers, especially in the context of the second year of the Master's program in Physical Education Teaching at the Basic and Secondary Education levels at the Faculty of Sport, University of Porto. This initial professional experience provided a first real contact with professional activity, preparing me for a future career built on a quality training process. During this period, I had the opportunity to apply theoretical concepts in a practical environment, facilitating significant personal and professional growth. This document aims to detail the evolution of the professional internship, highlighting the use of teaching models as an effective strategy for enriching the teaching-learning process. It emphasizes the use of technologies and the implementation of student-centered teaching models to address pedagogical challenges and promote active student participation in the learning process. Throughout the academic year, I participated in various activities with the school and in connection with the community. A part of my professional internship focused on analyzing the performance of secondary school students in invasion games using the Sports Education Model. Student performance was evaluated based on variables such as total appropriate, total inappropriate, total index, decision making, efficiency, effectiveness, game involvement, and game performance, with results indicating significant improvements in several studied variables.